The pivot player in handball and patterns detection – Instrument - Santos, F.M. (2009)
The theoretical context of this study is related with the observational methodology in the context of group games and sports studies, specifically Handball. Thus, this study intends to analyze the performance of the pivot player in the World Cup 2007 - Germany, European 2008 - Norway 2008 and China OG 2008 in a qualitative dimension. Our purpose was to get as much information as possible about the whole activity of the pivot player, by identifying sequential patterns of behaviour or conduct of the player/game, by using the sequential analysis. The observation instrument used to meet the main purpose of this work consists of a combination of format fields (FF) and systems of categories (SC). The codifications undertaken occurred in several handball games. Using this instrument we have shown that it provides support for the purposes for which it was developed, allowing more research into the offensive process of handball. Besides this, it makes possible the analysis of aspects of the game through perspective and contextual sequences, which we consider to be more accurate, to fit the "reality" of a game such as handball.